(untitled) (Fiep Bulletin - online, 2015)
the goal of this paper is to explore, based on a literature review, the role of Physical Education in the promotion of health, having as a basis a conception of health that involves the different dimensions of human beings (physical, emotional, social and spiritual). In the first part of the paper, I make a brief review about some benefits of physical activity to health. Next, I argue that although many researchers discuss health from a biological perspective, the condition of health is multidimensional. In other words, it involves the different aspects of human beings and relate to social, economical, educational and cultural aspects. Therefore, all these aspects need to be considered when we discuss the relationships between physical activity and health. In the second part of the text, I present some factors that usually determine the adhesionor lack of adhesionto physical activity, and argue that, even though the Physical Education alone cannot take care of this multiplicity of factors , it can, amongst other things promote: (1) a higher level of consciousness about the importance of physical activity to health and about the factors that usually determine sedentary behavior and adhesion to physical activity; (2) a taste for physical activity and the habit of practicing it; (3) the development of physical skills; (4) the kind of knowledge needed so that the individuals can get engaged in physical activity in regular, permanent and autonomous ways.